PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Feriyana Feriyana; Lukman Surjadi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research was conducted to obtain the results of the effect of firm size, leverage, profitability and liquidity on firm value. In this test, the researcher uses a manufacturing company listed on the Indonesia Stock Exchange. The technique used to collect samples is purposive sampling. A total of 78 companies were selected to assist with this research, and version 12 of the Eviews (Economic Views) program was used to manage the data. In the tests conducted, the researchers found that firm size and profitability had a significant and significant effect on firm value, while leverage and liquidity had no a significant and no significant effect on firm value.